(untitled) (CAHIERS MAGELLANES-NS, 2024)
Introduction Residency programs are defined as a structured educational activity comprising a series of clinical or other learning experiences in graduate medical education designed to prepare physicians to enter the unsupervised practice of medicine in a primary specialty by the Saudi Commission of health specialties) SCFHS. This study aims to assess patient understanding and attitudes toward resident participation in surgical and medical care within surgical specialties in Makkah hospitals. Methods A descriptive cross-sectional study was performed among patients at all surgical departments in Makkah, KSA (King Abdulaziz Hospital, Al-Noor Hospital, and King Faisal Hospital) through a self-report questionnaire that was simple, reserved participants' privacy, and easily understood by the general population. Results A total of 145 adult patients who had undergone surgery participated in the study survey. The majority of participants were female (55.9%), and the ages of participants were similar across all age groups; most of them were in the general surgery department (69%). More than 80% were able to define the resident physician accurately, 38.6% were able to define the resident's role, and 80% chose the attending physician as their main source of information regarding their surgery. Overall, 86% agreed that their care provided by resident physicians was under the supervision of the attending physician; and 85% agreed when asked about their comfort level with the idea of helping residents become better surgeons and physicians by allowing them to participate in all aspects of their care. 72.81% choose more or less agree when asked if they were examined by a resident physician prior to being seen by an attending physician during their hospital stay. 45.12% answer more or less disagree when asked if they feel that residents are lacked in medical knowledge, and 37% of patients disagreed that the resident physicians were unprofessional. Conclusion The majority of responses were able to define the resident's role accurately, and overall, this study sample is more or less agreed about the idea of resident physician participation in their medical and surgical care. We recommend a prior education of the patients on the specific role of caregivers during their hospital stay, and whether their attendance or performance is for a specific part or all of the surgery.